A new dual‐mode wideband circularly polarized rectangular dielectric resonator antenna coupled with stubs and asymmetric ground plane for WiMAX applications. Issue 9 (25th July 2017) - Kumar, Rajkishor; Chowdhury, Rakesh; Chaudhary, Raghvendra Kumar
Abstract: In this article, a new radiating stub microstrip feed has been investigated with asymmetrical ground plane for generation of circular polarization (CP) in a dielectric resonator antenna (DRA). Here, asymmetrical ground plane and 3 radiating stubs with microstrip feed line are used for generation of 2 different modes namely TE11δ and TE12δ in rectangular DRA. By using mode matching concepts, these modes are responsible for enhancing the impedance bandwidth (TE12δ ie, TE 12 δ x and TE 12 δ y ) and axial ratio (AR) bandwidth (TE11δ ie, TE 11 δ x and TE 11 δ y ) in proposed antenna. Designed antenna offers measured input impedance bandwidth (|S11 | < −10 dB) and AR bandwidth (AR < 3‐dB) of 44.78%, ranging from 4.6 to 6.9 GHz and 23.32%, ranging from 4.6 to 6.9 GHz, respectively. It has been observed that proposed antenna shows left‐handed CP fields in boresight direction with average gain of 3.15 dBic and radiation efficiency of 90.54%. Designed antenna is suitable for Wi‐MAX (3.3‐3.7 GHz) applications.